Murder your darlings : and other gentle writing advice from Aristotle to Zinsser - Clark, Roy Peter (Little, Brown Spark, 2020)
A collection of over a hundred writing tips gleaned from fifty popular writing books. Chapters are devoted to each key strategy. Author expands and contextualizes original authors' suggestions and shares how each tip helped other authors improve their skills.